Analysis of the magnetic properties of Ce3Pt23Si11: orthorhombic crystal field and mean-field approximation. (21st June 2018) - Galéra, R M; Opagiste, C; Amara, M; Toussaint, J-C; Lepetit, M-B; Rols, S
Abstract: We present here a quantitative analysis of the ground state and magnetic properties of Ce3 Pt23 Si11, based on a crystalline electric field description within the mean-field approximation. In this face-centered cubic compound, the point group symmetry at the Ce site is orthorhombic. One main difficulty in this low symmetry case is that the CEF potential for Ce 3+ ions is determined by five independent parameters, while only two magnetic excitations are observed by inelastic neutron scattering. Moreover the anisotropy of the magnetic susceptibility of the Ce ion, that permits an independent determination of the second-order CEF parameters is hidden by the cubic symmetry of the compound. A specific procedure is developed for this purpose that combines genetic algorithms and more conventional optimization methods. A set of CEF parameters is found that best reproduces the different experimental observations in both the paramagnetic and ferromagnetic phases of Ce3 Pt23 Si11 . The analysis accounts for two seemingly contradictory properties: a strong local anisotropy that aligns the moment along a fourfold axis and a rather weak anisotropy of the bulk magnetization with an easy threefold magnetization axis. Ce3 Pt23 Si11 is shown to be a model system where single site anisotropies compete within a crystal structure of overall high symmetry.